The Fear of Shipwreck and Humour: Turkish Bektashi and German Minnesanger (Minstrel) (Journal of Alevism-Bektashism Studies, 2014)
This article focuses on the two humourists, Bektashi and Minnesanger’s expe- riences during their voyage, and their sense of humour that they have added while narrating their stories in their works. The fear of shipwreck was very common in ancient travel works in the Mediterranean Sea; these works depicted such themes as the storms or disasters that the passengers, the crew, and the sailors encountered, in a humourous style. Humour changes our perceptions and prejudices in our lives by creating a virtual life free of problems(Moreau, J.,2005). Sample texts have been cho- sen from the Turkish humourist Bektashi’s selected works and German minstrel Min- nesanger’s complete works, dating back to the 13th century, entitled Mannessische Handschrift / Manesse Külliyatı, which is kept in Heidelberg University Library. The work, 428 pages long, includes the poetry of 140 poets who lived between the years 1150-60 and 1300. Tannhauser’s poems are on page 266 and 296. Because of several new editions, we are not so sure about the originality of the poems in the complete works of Manesse. According to the famous philologist Maria Grazia Cammarota, Manesse’s work is one of the most comprehensive and significant sources in terms of the analysis of the songs composed in different music according to the audience, the melodies and Tannhauser Crusade song